APPLICATION OF PAILKEM MODEL IN ROMAN NUMBERS TO IMPROVE STUDENT LEARNING CLASS IV SDN BUAH BATU LEMBANG WEST BANDUNG DISTRICT - Nurhajariah, Ratna Dewi (2013)
This research is motivated by low student learning outcomes in the cognitive domain of mathematics. It is directed by the average test scores that did not meet the minimum score criteria (KKM). The low student learning outcomes can not be separated from the lack of students' learning experiences gained from the learning process. This study focused on improving student learning outcomes in the cognitive domain through the application of Active, Innovative, Environment, Creative, Effective, and Fun Learning Model (AIECEF Learning Model/ PAILKEM). The purpose of this study is to get an idea of improving student learning outcomes in the cognitive domain as a result of the application of PAILKEM. In addition, this study also aimed at getting an overview of students' attitudes toward PAILKEM. The research method used is Classroom Actions Research (CAR) which adapted from model Kemmis and Mc. Taggart. The subjects were students of class IV SDN Buah Batu West Bandung Lembang district, amounting to 32 people. Data collected through testing and observation sheets. Based on the research results that the students' cognitive learning in general has increased after applying PAILKEM model. In the first cycle, the average score of students reached 57.38. Then the second cycle students' average score was 71 with an average normalized gain in the first cycle to the second cycle of 0.05 belonged to the lower classification. The third cycle students achieve an average 92.29 with the average normalized gain on the second cycle to third cycle 0.63 that belonged to medium clasification. It proved that there is an increasing score in the cognitive aspect of students after applying the PAILKEM model. Keywords: AIECEF Learning Model, student learning outcomes Penelitian ini dilatarbelakangi rendahnya hasil belajar siswa dalam ranah kognitif pada mata pelajaran matematika. Hal ini ditujukan dengan skor rata-rata ujian yang tidak memenuhi Kriteria Ketentasan Minimal (KKM). Rendahnya hasil belajar siswa tidak terlepas dari kurangnya pengalaman belajar siswa yang didapat dari proses pembelajaan. Penelitian ini difokuskan pada upaya peningkatan hasil belajar siswa pada ranah kognitif melalui penerapan Model Pembelajaran Aktif Inovatif Lingkungan Kreatif Efektif dan Menyenangkan (PAILKEM). Tujuan penelitian ini adalah untuk mendapatkan gambaran mengenai peningkatan hasil belajar siswa pada ranah kognitif sebagai penerapan hasil PAILKEM. Selain itu, penelitian ini juga bertujuan untuk mendapatkan gambaran tentang sikap siswa terhadap PAILKEM. Pada penelitian ini, metode penelitian yang digunakan adalah Penelitianu Tindakan Kelas (PTK) yang mengadaptasi model Kemmis dan Mc. Taggart. Subjek penelitian ini adalah siswa-siswi kelas IV SDN Buah Batu kecamatan Lembang Kabupaten Bandung Barat yang berjumlah 32 orang. Pengumpulan data dilakukan melalui tes dan lembar observasi. Berdasarkan hasil penelitian bahwa diperoleh hasil belajar siswa pada ranah kognitif secara umum mengalami peningkatan setelah diterapkan model PAILKEM. Pada siklus I skor rata-rata siswa mencapai 57,38. Selanjutnya pada siklus II skor rata-rata siswa mencapai 71 dengan rata-rata gain ternormalisasi pada siklus I ke siklus II sebesar 0,05 yang termasuk dalam klasifikasi rendah. Pada siklus III rata-rata siswa mencapai 92,29 dengan rata-rata gain ternormalisasi pada siklus II ke siklus III 0,63 dengan klasifikasi sedang. Hal ini menunjukkan bahwa terjadi peningkatan pada aspek kognitif siswa setelah diterapkan model PAILKEM. Kata Kunci: PAILKEM, hasil belajar siswa